Implementasi Hadis tentang Tanggung Jawab Pendidik dalam Kebijakan Profesionalisme Guru Madrasah Ibtidaiyah - Muhammad As’adurrofik; Nurfauziah Nurfauziah; Melly Aprilia; Mutia Rusda; Putri Aldizah; Siti Aisyah; Wardatul Jannah; Yazid Khoiri (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study discusses the implementation of hadiths regarding the responsibilities of educators in the professional policies of Madrasah Ibtidaiyah (MI) teachers. Hadiths emphasize that teachers have a moral and spiritual mandate to educate and shape the character of students in accordance with the standards of educators. This study aims to analyze the relationship between the values of professional responsibility and the values of educators' responsibility in the hadith with the standards of professionalism for MI teachers. The method used is a qualitative approach through a literature study of hadith books, Islamic education books, and education policy documents. The results of the study show that the values of trustworthiness, exemplary behavior, justice, and sincerity in the hadith are in line with pedagogical competence and professionalism as moral and religious obligations. The implication is that the integration of hadith values is important in the development of MI teachers in order to create competent educators with Islamic character